Regional Variation in Causes of Injuries among Terrorism Victims for Mass Casualty Events - James L Regens; Nick eMould; Amy eSchultheiss (Frontiers Media S.A., 2015)
The efficient allocation of medical resources to prepare for and respond to mass casualty events (MCEs) attributable to intentional acts of terrorism is a major challenge confronting disaster planners and emergency personnel. This research article examines variation in regional patterns in the causes of injures associated with 77,258 successful terrorist attacks that occurred between 1970 and 2013 involving the use of explosives, firearms and/or incendiaries. We hypothesize that the use of different weapons and tactics in each world region will result in significant variation in injury cause distributions. Indeed, we find that the distributions of the number of injuries by cause vary greatly among the 13 world regions identified within the GTD.